Veil as Religious Expression: A Sociological Study of University Students in Bangladesh - Mannan, Fouzia (Journal of ecumenical studies, 2022)
Currently, within feminist discourse, two major debates surrounding veiling or "purdah" take precedence, with one sect of feminist scholars identifying veils as oppressive and the other heralding veils as a source of agency as well as a freedom of choice. However, this dichotomy is not relevant to the Bangladeshi context and has given rise to a discrepancy between theoretical knowledge and real practice, urging further critical analysis of the changing role of veiling in the Global South generally and Bangladesh specifically, particularly among the youth and adolescent populations. Thus, this essay is based on the experience of teaching sociology in classes and interviewing university students who wear a veil at a Bangladeshi university. Increasing numbers of women, especially young women, can be seen wearing veils in Bangladesh, a drastic shift away from the decades following the nation's independence in 1971. Therefore, this essay will aim both to explore and to discuss reasons that incentivize young women, especially those who are studying, and to critique societal structures and phenomena (including religious behavior and gendered norms) regarding a different form of social attire. Thus, the research conducted was qualitative in nature, and the sample consisted of a select group of university students (using purposive sampling). Thirty-one in-depth interviews, case studies, and two focus group discussions were conducted. I note the ways in which patriarchy, capitalism, and globalization converge in the urban metropolitan setting of Dhaka, to encourage women across age and class divides to embrace religion as their dominant social identity over ethnic and national identities. Veiling in the context of Bangladesh is a complex multidimensional phenomenon; it is both an expression of religious piety and is deeply intertwined with issues of globalization, patriarchy, class, and feminine sexuality.